Knowledge Map : School-Level Issues - World Bank (Washington, DC, 2012)
Best practice exists for most issues relating to uses of information and communication technologies (ICTs) in education at the school level. Despite the wealth of documentation mentioned, little if any of this knowledge and information appears to have been incorporated into planning for and delivery of ICT in education initiatives in least development countries (LDCs), where the 'same old mistakes' are often made again and again. The greatest need related to this topic is for existing knowledge and information to be delivered to the relevant people in charge of ICT in education initiatives in LDCs, as well as those (in donor agencies, non-governmental organizations, and the private sector) who advise or contribute to such initiatives. Short workshops could be delivered to target countries preparing to scale up ICT in education initiatives to transmit such lesson learned.